BUSINESS MODELS, LIBRARIES AND EBOOKS - Serra, Liliana Giusti; Santarem Segundo, Jose Eduardo [UNESP] (Univ Federal Campina Grande, 2017)
This paper discusses the business models for licensing digital books by libraries with the proposal of identify their characteristics and application possibilities. From literature review, with time frame 2011 to 2016, are identified the digital content providers for libraries (publishers, distributors and content aggregators) and their procedures. The business models are presented, highlighting their characteristics and implications in the library management, particularly as regards the collection development, where the licensing process leads to a frailty as the loss of control about the titles present in the collections. The analyzed models covers the perennial and transitory licensing, exemplified in hiring models as Perpetual Acquisition, Signature, Demand Driven Acquisition (DDA), Short Term Loan (STL) and Evidence Based Selection (EBS). Under the transitory models are highlighted the possibility of content loan, made in order to meet immediate demands of patrons. The study also analyzes the licensing option offered by readers identified as Netflix for books and its possible uses. Fractionation of digital books is approached with the offer of book chapters, providing other applications possibilities in libraries. As a result, the study expected to provide subsidies to agents involved in the digital book with the guidance in the identification and selection of business models tailored to the needs of institutions and content hiring. The study concludes that all agents related to digital books should participate in the proposals, decisions and analysis of licensing arrangements in order to achieve a balance between those involved.
Keywords: Ebook; Licensed content; Business models; Collection management